Persepsi Petani Sayuran Dataran Tinggi Terhadap Pestisida Organik di Kelurahan Rurukan Kecamatan Tomohon Timur - Musa M. Dendegau; Eyverson Ruauw; Olfie L.S. Benu; Lorraine W. Th. Sondakh (COCOS, 2014)
ABSRACTMusa Dendegau. The Perception of Highland Vegetable’s Farmer About Organic Pesticide in Rurukan Village East Tomohon Subdistrict. Under guidance of E. Ruauw as chairman, and Benu Olfie and L.W.Th. Sondakh as members.The objective of this research is to find out the perception of highland vegetable’s farmer about organic pesticide in Rurukan Village East Tomohon Subdistrict.Sampling method used in this research is simple random sampling. This research uses primary and secondary data. Primary data are obtained from interviewed with 42 vegetable farmers using questioner to support the data collecting.Secondary data are obtained from village government/administration office to describe village profile. The data analysis isdescriptive analysis which analized with Likert Scale explained by using table.This research showed that based on Likert Scale analysis, the total perception score of vegetable farmer in Rurukan Village about organic pesticide is 1764, and perception index 56%, so farmer perception classified as less good. There were some farmer perception indicators about organic pesticideclassified as worse, which is indicator about organic pesticide that can increase farmer’s income and welfare, and farmer perception about special market who buy organic products from Rurukan. For some indicator, like land compatibility, complexity level to make organic pesticide, compatibility with Rurukan teritory, and product price, the farmer perception classified as good. Farmer perception classified as less good for some indicator, which were the increaseof productivity, compatibility to habit and need of farmer, complexity and practicality in organic pesticide using, market supply, triability for every kind of plant and added value of output.